Surface Functionalization of CsPbBr3 Νanocrystals for Photonic Applications - Manoli, Andreas; Papagiorgis, Paris; Sergides, Marios; Bernasconi, Caterina; Athanasiou, Modestos; Pozov, Sergey; Choulis, Stelios A.; Bodnarchuk, Maryna I.; Kovalenko, Maksym V.; Othonos, Andreas S.; Itskos, Grigorios (My University, 2021)
The primary obstacle to the use of lead halide perovskite nanocrystals (NCs) in optoelectronics is the inability of traditional ligand engineering approaches to provide robust surface passivation. The structural lability can be mitigated by employing different ligands such as long-chain quaternary ammonium and zwitterionic surfactants. Here, we report a comprehensive study that probes the impact of such surface passivation routes on the optoelectronic properties of weakly confined CsPbBr3 NCs. Spectroscopy unravels clear correlations of various photophysical figures of merit with the ligand type used. Compared to NCs decorated by conventional oleic acid/oleylamine ligands, passivation with the quaternary ammonium or zwitterionic surfactants increases the NC solid-state emission yield by up to 40% by halving the average trap depth and increasing by 1.5 times the exciton binding energy. Furthermore, the aforementioned ligands better preserve the size of NCs in thin films, as shown by the absence of significant NC aggregation and the confinement-induced increase by a factor of 2 of the Fröhlich interaction between excitons and optical phonons. The suitability of ligands for photonics is finally assessed by probing metrics, such as the amplified spontaneous emission threshold, the moisture tolerance, and the photoconductivity and electroluminescent performance of lateral and vertical devices, respectively.